2011
DOI: 10.1007/s00125-011-2399-7
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the RNA-binding protein ARE/poly(U)-binding factor 1 (AUF1) in the cytotoxic effects of proinflammatory cytokines on pancreatic beta cells

Abstract: Aims/hypothesis Chronic exposure of pancreatic beta cells to proinflammatory cytokines leads to impaired insulin secretion and apoptosis. ARE/poly(U)-binding factor 1 (AUF1) belongs to a protein family that controls mRNA stability and translation by associating with adenosine-and uridine-rich regions of target messengers. We investigated the involvement of AUF1 in cytokine-induced beta cell dysfunction. Methods Production and subcellular distribution of AUF1 isoforms were analysed by western blotting. To test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Chronic exposure to inflammatory conditions leads to beta cell dysfunction and apoptosis [32,44,45]. A recent investigation has revealed that the level of miR-34a increased concomitantly in cytokinetreated MIN6 cells and human pancreatic islets, and contributed to beta cell dysfunction [32].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic exposure to inflammatory conditions leads to beta cell dysfunction and apoptosis [32,44,45]. A recent investigation has revealed that the level of miR-34a increased concomitantly in cytokinetreated MIN6 cells and human pancreatic islets, and contributed to beta cell dysfunction [32].…”
Section: Discussionmentioning
confidence: 99%
“…47 ARE/ poly(U)-binding factor 1 (AUF1), the best-characterized RBP that controls mRNA stability and translation by associating with AU-or U-rich sequence elements (ARE) frequently found within the 3'-UTR, was found to be involved in the cytotoxic effects of proinflammatory cytokines on pancreatic β cells. 48 Exposure of pancreatic β-cells to cytokines caused translocalization of (PI3K), phosphoinositide-dependent kinase 1 (PDK1) and the protein kinase AKT, and thereby regulates not only glucose and lipid metabolism but also cellular proliferation and apoptosis. [15][16][17][18][19][20][21][22][23] Indeed, studies of animal models with targeted mutations in genes that encode mediators of insulin signaling have revealed that insulin signaling plays a central role in metabolic actions in insulin-sensitive tissues and contributes to the pathogenesis of T2DM.…”
mentioning
confidence: 99%
“…Roggli and co-workers observed that MIN6 cells and human islets produce all the different AUF1 isoforms [37]. Exposure of MIN6 cells to cytokines induces their translocation from the nucleus to the cytosol, indicating their activation.…”
mentioning
confidence: 98%
“…Identification of novel molecules that modulate this cell death pathway will hopefully provide alternative approaches to prevent beta cell apoptosis in early type 1 diabetes. In this issue of Diabetologia, Roggli and colleagues investigated the role of the RNA binding protein ARE/poly(U)-binding factor 1 (AUF1) on cytokine-mediated beta cell apoptosis [37]. This protein interacts specifically with adenosine-and uridinerich elements (ARE) located in the 3′ untranslated region (UTR) of target mRNAs, thus regulating their stability [38].…”
mentioning
confidence: 99%
See 1 more Smart Citation